Optimal Ordering Policy for Seasonal Products/ Newly Launched Fashion Items under Periodic Review - Sujan Chandra (Current Approaches in Science and Technology Research Vol. 1, 2021)
In this paper, we study some features that are likely to be associated with certain types of inventory, like inventory of seasonal products, newly launched fashion items, electronic goods, mobile phones, etc. A periodic review inventory model is developed with ramp type demand rate. When the inventory on hand is zero, the inventory manager offers customers who are prepared to backorder a discount.By lowering the total cost in a replenishment interval, the best ordering policy and the best discount offered for each backorder may be found.